A Smart Wheelchair Robotic System With Health Monitoring And Communication Aid For Paralyzed Person - et. al., Iswaramoorthy U, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Hand gesture controllers are used for controlling the smart wheelchair robotic system with health monitoring and emergency communication aid. many people in the world has lost the ability to control the upper limbs and the lower limbs due to quadriplegia, paralyses or ageing factors. These types of the user requires specialized controlling systems for using an electrical wheelchair rather than using the traditional control by the joystick. In this type of wheelchair control system, hand gesture-controlled mobile wheelchair robots can be used as powerful helping system for the severely disabled people in their daily life, especially for helping them move voluntarily. In this project, we would be using the hand gesture controlled wheel chair robotic system. The hand gesture controlling system uses the movement of our hands to operate the system. Continous health monitoring is maintained and provided to help during the emergency conditions. Emergency alerting and aiding system helps in the alerting the nearby people and send alert messages to the hospital and close family members